القتل الخطأ في الفقه الإسلامي - احشيفة, آسيا; عبداللاوي, حكيمة; هقي, سمية (جامعة الوادي - University of Eloued, 2013)
Summary Arabic search Humans are exposed to an error, but one has to return to what it is to return to God Almighty, and Kamal Islamic law they painted an outline to take care of the interests of individuals and groups, and likes the wisdom of the Almighty that is prescribed for the sins of what brought and can remove the remains slave obedient pure from sins and misdeeds. This research included doctrinal subject matter, which has a relationship with the same man who is the successor of God on earth. Interesting in terms of a statement by the Islamic Sharia. Therefore, the scholars of Islamic sects have directed their attention towards the search for means to protect rights in himself Vmutir on the statement of what humans erase all his sins and make them the satisfaction of of Ruba worlds. . We have explained in this research subject of crime in general and self-Felony special introductory Kmbges, then a statement of manslaughter and his sentence prescribed by Shara, of penance and deprivation of parental inheritance and wills. Imams were able to clarify the doctrines contrast to kill financial self error and statement of fact penance. This punishment initiated by one in order to atone for his sins and can remove to keep clean.
مذكرة ليسانس